Understanding of Santri Regarding Quranic Verses as Prayers within Hizib Nahdlatul Wathan and Its Implications for Children's Education in Daily Life : (A Study of Living Quran at the Islamic Center NW Tanjung Riau Batam Boarding School) - Ulyan Nasri; Parhul Khairi; Ahmad Syukri; Masiyan Masiyan (Jurnal Ilmiah Profesi Pendidikan, 2023)
This qualitative research explores the understanding of santri (students) regarding Quranic verses as prayers within Hizib Nahdlatul Wathan and its implications for children's education in daily life. The study is conducted at the Islamic Center NW Tanjung Riau Batam Boarding School. Through in-depth interviews, observations, and document analysis, the study examines how santri comprehend and apply Quranic verses as prayers within Hizib Nahdlatul Wathan and the subsequent impact on children's education. The findings reveal that santri exhibit a profound understanding of Quranic verses as prayers within Hizib Nahdlatul Wathan. They perceive these verses not only as supplications for blessings and protection but also as a means to strengthen their spiritual connection with Allah. This understanding influences their behavior, attitudes, and decision-making in their daily lives. The implications for children's education are extensive, including the cultivation of moral awareness, empathy, and resilience. The integration of Quranic teachings contributes to the holistic development of children, enabling them to embody Islamic values and principles in their interactions and choices. This research contributes to the broader understanding of the role of religious teachings in shaping character, ethics, and values among young learners. It underscores the significance of incorporating Quranic teachings into educational practices to nurture individuals who are both knowledgeable and morally grounded. Ultimately, this study emphasizes the potential of religious education to create well-rounded individuals who contribute positively to society while remaining steadfast in their faith.